Islamic Perspectives in EFL Teaching - Kalayo Hasibuan Hasibuan; Dicky Isna Permana; Elvia Mutiara Ikhsani; Fadhillah Pebriani Tanjung (Journal of Innovative and Creativity, 2025)
This study delves into the integration of Islamic values within English as a Foreign Language (EFL) instruction, offering a comprehensive examination of how religious and cultural principles from the Qur’an, Hadith, and Islamic pedagogical philosophy can enrich language education. Rather than viewing language acquisition as a standalone objective, this paper advocates for a more holistic approach—one that incorporates Islamic ethics, communication norms, and cultural identity into the curriculum. Central areas explored include the infusion of Islamic cultural narratives into teaching practices, the adaptation of instructional materials to ensure alignment with religious principles, and the nurturing of language skills framed within ethical and spiritual dimensions. The paper also examines the essential role of educators as moral guides and curriculum developers across various levels of educational structure. Ultimately, this paper argues that by embedding Islamic values into EFL instruction, educators can produce learners who are linguistically proficient and spiritually grounded, preparing them to navigate both global communication and Islamic ethical life.